The Public Mapping Project : How Public Participation Can Revolutionize Redistricting - Altman, Micah; McDonald, Michael, 1967-; Project Muse. (Ithaca : Cornell Selects, an imprint of Cornell University Press, 2018)
"About the Public Mapping Project's DistrictBuilder platform, which allows citizens to become involved in the process of drawing congressional districts and create their own congressional maps in an easy-to-use way"--
Introduction -- A history of public mapping -- Planning for public mapping -- DistrictBuilder -- Public mapping and redistricting reform.
Description based on print version record.
Keywords: United States. -- Congress; United States. -- Congress -- Election districts -- Maps; Election districts -- Maps; Digital mapping; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Cartographie par ordinateur; Digital mapping; Election districts -- United States -- Maps; United States; Maps; Electronic books